Characterization of a non‐thermally operated electrosurgical argon plasma source by electron spin resonance spectroscopy. Issue 2 (12th November 2018) - Weiss, Martin; Utz, Raphael; Ackermann, Michael; Taran, Florin‐Andrei; Krämer, Bernhard; Hahn, Markus; Wallwiener, Diethelm; Brucker, Sara; Haupt, Michael; Barz, Jakob; Oehr, Christian
Abstract : Non‐thermal plasma treatment is one of the promising options for local anti‐neoplastic treatment of dysplastic lesions and early intraepithelial cancer. Primarily, the antiproliferative properties are driven through the generation of reactive oxygen and nitrogen species. In this study, we investigated the amount and distribution of reactive species generated by a non‐thermally operated electrosurgical argon plasma source using electron spin resonance (ESR) spectroscopy. During the plasma treatment of both, aqueous solution and solid human preputial tissue an increasing amount of different oxygen‐ and carbon‐centered radicals was detected. However, and most probably due to spin trap degradation by the high energy input and the increase of reactive components in aqueous solution, the ESR signal decreased after treatment times exceeding 10 s. Abstract : Non‐thermally operated electrosurgical argon plasma sources reveal a potent emergence of reactive species and may be suitable for usual cold atmospheric plasma applications in plasma medicine. The vigorous generation of reactive plasma components of these plasma sources, being the main trigger for plasma related cell phenomena, may enable efficient treatment of precancerous and cancerous lesions.